Mecanismos neurológicos e sistêmicos envolvidos na patogênese da listeriose e impactos do uso de curcumina livre e nanoencapsulada na infecção in vivo - Jaguezeski, Antonise Mariely (2021)
Foodborne zoonotic disease, listeriosis contains numerous gaps in knowledge regarding its pathogenic mechanisms. In addition, the problem of bacterial resistance requires potential alternatives to treatment. The aim of this study was to verify changes in the cholinergic, purinergic, redox status and energy metabolism systems in listeriosis; as well as verifying the effects of free and nanoencapsulated curcumin in experimentally infected animals. In Experiment I, 10 cattle were used, 5 of which were infected with L. monocytogenes. Blood samples were collected on days 7 and 14 post-infection (PI) to assess acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) activity. AChE activity was measured in central nervous system (CNS) on day 14 PI, time of euthanasia. Cerebral cortex, brainstem, cerebellum and spinal cord were used to measure AChE, NTPDases, ADA, PK, AK, CK, Na+/K+ATPase activities and redox status. In experiment II, gerbils were usedː with adult gerbils, an experimental study of the mechanisms of infection was carried out, similar to that carried out with cattle, with an infected group and a control group, euthanized at 6 and 12 days PI. After 12 days PI, the antibacterial action of PCR treatments on the spleen, oxidative stress, inflammatory and energy metabolism markers were evaluated. With young gerbils, a control group (group T0), infected without treatment (group T1), infected treated with free curcumin (group T2) and infected treated with nanocapsules curcumin (group T3) were formed. In experiment I, there was a positive PCR for the bacteria in the liver and CNS. In none of the experiments the animals showed clinical signs. AChE activity in blood, spleen, cerebral cortex and cerebellum was lower in those infected, as was BChE in serum 14 days PI. NTPDase, 5'-nucleotidase and ADA activity had lower activity on the same day in most brain structures, not changing in the spinal cord. Mitochondrial CK activity was higher and cytosolic lower in all brain structures; as well as PK and Na+/K+ATPase activity. In experiment II with adult gerbils, the liver and heart showed lower PK and Na+/K+ATPase activity, and in the heart, mitochondrial and cytosolic CK had lower activity in those infected. The ADA activity was lower in the infected brain as well as the AChE activity, while there were higher levels of ROS and lower levels of CAT and SOD in this group. In the experiment with young gerbils, PCR for Listeria in the spleen was positive at T1 (6 of 6), T2 (2 of 6) and T3 (5 of 6). In liver, PK activity was lower in T1 and T2, as well as Na+/K+ATPase activity. The group treated with nanoencapsulated curcumin had lower lipoperoxidation than the other groups, while all infected groups had higher ACAP. We conclude that subclinical L. monocytogenes infection causes alterations in the cholinergic, purinergic, redox and energy metabolic state in target and non-target organs, which contribute to the pathogenesis of the disease. There is a protective immunomodulatory response through the enzymatic activity of these systems, which seek to reestablish homeostasis in inflammation. Free curcumin showed an antibacterial effect, but the nanoencapsulated form was able to minimize changes in energy metabolism and lipoperoxidation.